Menjadi Pendidik Profesional di Abad 21 - Kamila Kamila (Direktorat GTK Madrasah Ditjen Pendis Kementerian Agama Republik Indonesia, 2023)
The purpose of this paper is to explain how far an educator can become a professional educator, able to compete, willing to work hard and learn about technology and seek information from various sources and dare to face challenges in the 21st century. The results of this writing show that professional teachers are able to change their teaching patterns in accordance with the times, know how to use learning methods that are more creative and innovative, work professionally, are smart and able to combine technology and learning, are more skilled, disciplined and responsible so as to produce students who are smart, have Islamic character, students who are able to think critically in solving everyday problems. As well as being able to develop learning and transfer knowledge perfectly. In conclusion, education will run optimally and be successful if all components succeed in running the education system properly. Learners or students will become students who excel, have character, are critical in facing the challenges of the 21st century, if a teacher is able to become a professional educator or teacher. They want to develop and learn to become professional teachers, aware of their duties and responsibilities. There are many ways that an educator or teacher can do if they want to develop themselves into a professional teacher, because the government is actually trying to provide the best for educators, education staff and students Abstrak Tujuan penulisan ini adalah menjelaskan sejauh mana seorang pendidik bisa menjadi pendidik yang professional, mampu bersaing, mau bekerja keras dan belajar tentang teknologi serta mencari informasi dari berbagai sumber serta berani menghadapi tantangan di abad 21. Hasil penulisan ini menunjukkan bahwa guru professional mampu mengubah pola mengajarnya sesuai dengan perkembangan zaman, tahu menggunakan metode pembelajaran yang lebih kreatif dan inovatif, bekerja dengan professional, pintar dan mampu menggabungkan antara teknologi dan pembelajaran, lebih terampil, disiplin dan bertanggung jawab sehingga menghasilkan peserta didik yang cerdas, berkarakter islami, siswa yang mampu berfikir kritis dalam memcahkan masalah dilingkungan hidunya sehari-hari. Serta mampu mengembangkan pembelajaran dan mentransfer ilmu pengetahuan dengan sempurna. Kesimpulannya Pendidikan sekiranya akan berjalan dengan maksimal dan berhasil jika semua komponen berhasil menjalankan sistem pendidikan dengan baik. Peserta didik atau siswa akan menjadi siswa yang berprestasi, berkarakter, kritis dalam menghadapi tantangan abad 21, jika seorang guru mampu menjadi tenagan pendidik atau guru yang profesional. Mereka mau berkembang dan belajar menjadi guru profesional, sadar akan tugas dan tanggung jawabnya. Banyak cara yang dapat dilakukan seorang pendidik atau guru jika ingin mengembangkan dirinya menjadi seorang guru profesional, karena sejatinya pemerintah berusaha untuk memberikan yang terbaik untuk pendidik, tenaga kependidikan dan peserta didik